For example if I want to show the equation for $x \rightarrow y$, using truth tables it is the same as:

$$(\neg x \wedge \neg y) \lor (\neg x \wedge y) \lor (x \wedge y)$$

Is there a methodical way to reduce something like this to its simple form $\neg x \lor y$?


You can prove this way: \begin{align} ((\neg x \wedge \neg y) \lor (\neg x \wedge y) \lor (x \wedge y))&\iff ((\neg x\land(\neg y\lor y))\lor (x \wedge y)) \\ &\iff((\neg x\land 1)\lor (x \wedge y)) \\ &\iff(\neg x\lor (x \wedge y)) \\ &\iff((\neg x\lor x)\land (\neg x\lor y)) \\ &\iff(1\land (\neg x\lor y)) \\ &\iff(\neg x\lor y) \end{align}

  • $\begingroup$ Wow, I didn't know you could use distributive property like that! $\endgroup$ – Sean Hill Dec 27 '15 at 23:27

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.